Analysis of The Value of Panji Village Shaking Tradition for Performing Arts Costume Design in Singaraja City - Putu Ariella Peggy Sabella; I Gede Mugi Raharja; Anak Agung Gede Rai Remawa (CV. Syntax Corporation Indonesia, 2024)
The Megoak-goakan tradition is a tradition in the form of a traditional game originating from Panji Village, Buleleng Regency, Bali. This tradition has now developed into a performance art in the form of dance, and drama. The tradition of megoak-goakan was developed into a performing art for preservation efforts and introduced the tradition of Megoak-goakan to the younger generation. The tradition of gowing has values implicit in it and is conveyed through the performing arts to the audience. The value in the tradition of goak-goakan can also be conveyed through the costumes used. The selection of the right costume design can be an intermediary message to the audience. This study aims to analyze the values that exist in the tradition of rocking Panji Village to become the basis for designing costumes for the performing arts tradition of rocking in Singaraja City. This research is a qualitative research with the data in this study being primary and secondary data. The method of collecting this research data is in the form of observation, interviews and literature. The purpose of this study is to find value in the Megoak-goakan Tradition that can help in making costume designs for Megoak-goakan performing arts in Singaraja City.